Β‐molybdenum carbide/carbon nanofibers as a shuttle inhibitor for lithium‐sulfur battery with high sulfur loading. (13th August 2019) - Zhuang, Ruiyuan; Yao, Shanshan; Liu, Menghao; Wu, Jianchun; Shen, Xiangqian; Li, Tianbao
Summary: We report the synthesis of β‐molybdenum carbide/carbon nanofibers (β‐Mo2 C/CNFs) by electrospinning and annealing process, when exploited as an interlayer in Li‐S batteries, demonstrating significantly improved electrochemical behaviors. The synthesized β‐Mo2 C/CNFs with 3D network structure and high surface area are not only conducive to ion transport and electrolyte penetration but also effectively intercept the shuttle of lithium polysulfide by polar surface interaction. Moreover, the reaction kinetics of the batteries enhanced is due to the presence of β‐Mo2 C, promoting the solid‐state polysulfide conversion reaction in the charge‐discharge process. Compared with the batteries with CNF interlayer and without interlayer, the batteries using a β‐Mo2 C/CNFs interlayer with a sulfur loading of 4.2 mg cm ‐2 delivered excellent electrochemical performance because of a facile redox reaction during cycling. The discharge capacity at the first cycle at 0.7 mA cm −2 was 1360 mAh g −1, maintaining a specific capacity of 974 mAh g −1 after 160 cycles. Furthermore, it showed a high‐rate capacity of 700 mAh g −1 at 14 mA cm −2 . This work demonstrates the β‐Mo2 C/CNFs as a promising interlayer to exploit Li‐S battery commercialization. Abstract : A conductive β‐molybdenum carbide/carbon nanofibers (β‐Mo2 C/CNFs) membrane acting as a pseudo‐ upper current collector and a shuttle inhibitor not only significantly reduces the charge transfer resistance of sulfur cathodes, but also localizes and retains the dissolved active material during cycling.